FORMATION OF THE COMPUTER COMPETENCE OF FUTURE FINANCIERS IN THE PROCESS OF LEARNING ECONOMETRICS - Hlushak, Oksana; Bodnenko, Dmitry; Semenyaka, Svetlana (Educological discourse, 2018)
The article reveals the peculiarities of the formation of the computer competence of future financiers in the process of learning econometrics. The components of the computer competence of future finance specialists are determined. As a result of the study, it was determined that the process of forming the computer competence of future finance professionals in the process of teaching econometrics should be presented as a model consisting of the following components: purpose, principles (system and consistency, visibility, communication theory with practice, priority of humanistic values, democracy and individualization), approaches (active, competent, cultural, personally oriented and systemic), means (electronic training course), pedagogical conditions (motivational support of the student's activity, based on the interdisciplinary nature of the discipline of econometrics: knowledge of certain sections of mathematics, economics and information technologies; updating of content of discipline and implementation of a training complex on the basis of the electronic training course in Moodle; attracting future financiers to perform professional tasks with the use of information technologies), forms (training sessions (lectures, practical classes, individual classes, electronic training courses), postures classroom work (teaching and research, independent study work is based on the use of information technology), self-education), criteria (motivation, contents, evaluative-effective), levels (elementary, middle, and high enough), result.